Beneficial haemodynamic effect of indomethacin during endotoxin shock in anaesthetized pigsputative involvement of nitric oxide? - T. Mózes; E. M. van Gelderen; E. J. Mylecharane; P. R. Saxena (Hindawi Limited, 1995)
Endotoxin shock was induced in 31 anaesthetized pigs by infusion of 5 μg/kg of Escbeicbia coli endotoxin (LPS) over 60 min into the superior mesenteric artery. Fifteen of these pigs died within 30 min of the start of LPS infusion whereas the remaining 16 survived the experimental period of 2 h. In a group of nine pigs indomethacin (2 mg/kg, i.v.)was inected 20-25 rain after the start of LPS infusion at which time mean arterial blood pressure (MABP) had decreased below 40 mmHg indicating imminent death. Indomethacin immediately reversed the hypotension. In another group of five pigs, NG-nitro L-arginine-methyl ester (L-NAME, 1 and 3 mg/kg)was iniected 10 and 5 min, respectively, before the expected death without any beneficial effect on the hypotension. Three rain after the last dose of L-NAME, indomethacin (2 mg/kg, i.v.) was iniected. In three animals the hypotension was reserved by indomethacin, although this beneficial effect was delayed in comparison with the LP-Streated group not receiving L-NAME. Four pigs were pretreated with L-NAME, 3 mg/kg, i.v., 10 min prior to LPS infusion. All pretreated animals tended to die within 30 min of the start of the LPS infusion. Five rain before the expected death (20-25 rain after the start of LPS infusion) indomethacin (2 mg/kg) was inected. In three of these animals indomethacin reversed hypotenston and prevented death. Interestingly, this rise in the MABP developed very slowly. These results suggest that the beneficial effect of indomethacin in endotoxin shock might be related partially to interference with nitric oxide, which is not the only factor determining blood pressure levels during endotoxic shock.